Estimation Of Gene Action And Combining Ability In Rice (Oryza Sativa L.) Through Line X Tester Analysis Carried Over Environments (Applied Biological Research, 2015)
Line x tester analysis over environments was carried out in rice during  2011 and 2012, with 9 lines, 3 testers and 27 hybrids thus generated.  Analysis of variance revealed significant differences among genotypes for  most of the characters studied. Mean squares due to G x E interaction and  environmental component was observed to be significant for all the traits.  Analysis of variance further revealed significant mean squares for general  and specific combining ability for all traits. The mean sum of squares due  to environments was also significant for most of the traits. The variances of  SCA were higher than GCA variances for some of the characters but  reverse was true for other characters, thus showing importance of both  additive and non-additive genetic components. The GCA estimates for  grain yield plant-1 suggested that the parents ‘K-08-60’, ‘K-08-61’ and  ‘Pusa Sugand-5’ as promising on the basis of significant positive GCA  effects at pooled levels.
Keywords: Combining ability; environmental interaction; gene action; hybrid rice; line x tester